2017
DOI: 10.1021/acssuschemeng.7b02388
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Chitosan–SiO2 Nanoparticles: Synthesis, Characterization, and CO2 Adsorption Capacity

Abstract: Mesoporous chitosan–SiO2 nanoparticles (NPs) were successfully synthesized. The prepared nanoparticles were characterized using TEM, FTIR, XRD, TGA, EDX, and (CHN) elemental analysis. From TEM micrograph, chitosan–SiO2 NPs were sphere-like, pretty uniformly distributed with coarse surface. The average size of chitosan–SiO2 NPs was determined as 211 nm with DLS, which was confirmed by TEM. The mesoporous structure of chitosan–SiO2 NPs was characterized with N2 adsorption/desorption measurements. BET surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 38 publications
4
53
0
3
Order By: Relevance
“…[17] Although initial adsorption heat of PG-K is the highest, its low-pressure CO 2 capacity is much lower than the other two samples due to weak adsorption potential between CO 2 molecules and the carbon walls (the micropore size of PG-K is dominantly focusedo n% 0.9 nm). The dynamic selectivity S CO2/N2 is estimated to be about4 54 for PGC-K,w hichi sm uch higher than those experimental results reported in the literature for porousc arbons (Table S2 in the Supporting Information), MOFs [18] and other adsorbents such as porouso rganic polymers, [19] zeolite [20] and silica nanoparticles [21] under similarc onditions. In addition, mild interactions between CO 2 molecules and PGC-Kw ould decrease the cost of regeneration in separation process.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…[17] Although initial adsorption heat of PG-K is the highest, its low-pressure CO 2 capacity is much lower than the other two samples due to weak adsorption potential between CO 2 molecules and the carbon walls (the micropore size of PG-K is dominantly focusedo n% 0.9 nm). The dynamic selectivity S CO2/N2 is estimated to be about4 54 for PGC-K,w hichi sm uch higher than those experimental results reported in the literature for porousc arbons (Table S2 in the Supporting Information), MOFs [18] and other adsorbents such as porouso rganic polymers, [19] zeolite [20] and silica nanoparticles [21] under similarc onditions. In addition, mild interactions between CO 2 molecules and PGC-Kw ould decrease the cost of regeneration in separation process.…”
Section: Resultsmentioning
confidence: 55%
“…Dynamic CO 2 capacity is very close to the equilibrium adsorption value (1.1 mmol g À1 ) of the single component CO 2 at the partial pressure of 0.17 bar.T his implies that CO 2 stillp referentially adsorbs onto the adsorbent over N 2 ,e ven in ad ynamic flow situation. The dynamic selectivity S CO2/N2 is estimated to be about4 54 for PGC-K,w hichi sm uch higher than those experimental results reported in the literature for porousc arbons ( Table S2 in the Supporting Information), MOFs [18] and other adsorbents such as porouso rganic polymers, [19] zeolite [20] and silica nanoparticles [21] under similarc onditions. PGC-K reaches at rade-off between CO 2 capacity and selectivity under ad ynamic flow situation due to its interconnectedm acroporous structure coupled with appropriate micropores and CO 2 -philic nitrogen species.…”
Section: Resultsmentioning
confidence: 55%
“…Figure 7 shows the evolution of the DRX spectra of the chitosan films as a function of the nanoparticle concentration. It has been reported that the characteristic peaks of chitosan are located around 2θ values of 8°, 11°, 18°, and 23° [3,15,32,33,41,[43][44][45][46][47], where the first two peaks (8°and 11°) indicate a hydrated crystallite structure due to the integration of water molecules in the crystal lattice; the peak at 18°is attributed to the regular chitosan crystal lattice, and the peak around 23°corresponds to an amorphous chitosan structure [41]. Some studies report a diffraction peak around 15°which is attributed to an anhydrous crystalline network [33].…”
Section: Characterization Of Chitosan Filmsmentioning
confidence: 99%
“…C-H in-plane vibrations, C-H stretching vibrations and N-H in-plane vibrations appeared at 1296, 916, and 780 cm −1 [12,[16][17][18]. In the case of HMSNs, the characteristic peaks of water and silanol OH stretching (3436 cm −1 ), hydrogen bonding of water molecules on silica (1628 cm −1 ), Si-O-Si symmetric stretching (791 cm −1 ), and Si-O asymmetric stretching (1085 cm −1 ) could be observed [1,[9][10][11][12][13][14][15][16][17][18][19][20][21]. Moreover, PPy/HMSNs not only had the characteristic peaks of HMSNs but also the characteristic peaks of PPy.…”
Section: Resultsmentioning
confidence: 94%